Suriname. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Suriname during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as horticulture, natural resource management, agribusiness, solar energy, hydroponic production, protected agriculture and resilience against climate change, as well as the use of organic gardens. Likewise, work was done on the automation of processes and on the management of water resources, such as the collection of rainwater, to mitigate the impact of water sources contaminated by mercury. Finally, the use of the Perone Hive technology was supported, in beekeeping and in the use of the Rice Intensification System (SRI), in order to improve rice production.